Culture of Hybrid Tilapia: A Reference Profile - Frank A. Chapman (EDIS)
This document is about Tilapia, which is a generic term used to designate a group of commercially important food fish belonging to the family Cichlidae; the expression is derived from the African native Bechuana word "thiape," meaning fish. Cichlids are classified in the large order Perciformes, and inhabit the fresh and brackish waters of Africa, the Middle East, coastal India, Central and South America. True tilapias, however, are native only to Africa and the Middle East. Although exotic to the United States, populations of tilapia are now established in Arizona, California, Hawaii, Florida, Nevada, North Carolina, and Texas. First published July, 1992.